2022
DOI: 10.1364/oe.458708
|View full text |Cite
|
Sign up to set email alerts
|

Periodic evolution of the out-of-phase dipole and the single-charged vortex solitons in periodic photonic moiré lattice with saturable self-focusing nonlinearity media

Abstract: We survey the propagation properties of the out-of-phase (OOP) dipole solitons and the single-charged vortex (SCV) soliton in a periodic photonic moiré lattice with θ = arctan ⁡ ( 3 / 4 ) under self-focusing nonlinearity media. Since the rotation angle, periodic photonic moiré lattices have peculiar energy band structures, with highly flat bands and the bandgaps being much more extensive, which is very favorable for the realization and stability of the solitons.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Under the nonlinear condition of V 0 = 30V, the transport properties of the OOP dipole beams in the repulsive defect photonic moiré lattice with θ= arctan (3/4) and ε = −0.5 are investigated comprehensively. The input beams could remain localized in the repulsive defect moiré lattice, as can be seen from the side-view of the beams in figure 4(a) (as previously reported in the paper [27]). Figures 4(b1)-(b4) shows the intensity distribution and phase structure at different distances, and the corresponding interferograms are shown in figures 4(c1)-(c4), which are obtained by interfering the OOP dipole beams with an inclined plane wave.…”
Section: Transmission Characteristics Of the Oop Dipole Beamssupporting
confidence: 74%
See 2 more Smart Citations
“…Under the nonlinear condition of V 0 = 30V, the transport properties of the OOP dipole beams in the repulsive defect photonic moiré lattice with θ= arctan (3/4) and ε = −0.5 are investigated comprehensively. The input beams could remain localized in the repulsive defect moiré lattice, as can be seen from the side-view of the beams in figure 4(a) (as previously reported in the paper [27]). Figures 4(b1)-(b4) shows the intensity distribution and phase structure at different distances, and the corresponding interferograms are shown in figures 4(c1)-(c4), which are obtained by interfering the OOP dipole beams with an inclined plane wave.…”
Section: Transmission Characteristics Of the Oop Dipole Beamssupporting
confidence: 74%
“…However, there are many open issues that remain to be explored. For example, the evolution of the SCV and doublecharged vortex (DCV) in square photonic lattices [37] and photonic moiré lattices [27] has been thoroughly studied. How do vortex beams (SCV and DCV) evolve in the repulsive defect moiré lattice?…”
Section: Transmission Characteristics Of the Oop Dipole Beamsmentioning
confidence: 99%
See 1 more Smart Citation
“…By tuning the rotation angle, the conductive properties of graphene can be adjusted between superconductors and topological insulators, which opens up new fields for * Author to whom any correspondence should be addressed. condensed matter physics and photonics [6][7][8][9][10]. In photonics, moiré lattice pattern is reported by the incoherent superposition of two identical sublattice beams [11,12], e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, it is also demonstrated that the two-dimensional aperiodic moiré photonic lattice supports the localization of the probe beam due to the existence of a large number of flat bands, while the periodic lattice structure leads to the delocalized propagation of the beam due to the absence of flat bands [19]. Recently, researchers have found that the coherent superposition of two sets of relatively rotating light fields may lead to the moiré-like photonic lattice, which also follows the Pythagorean equation or the Diophantine equation, and the localization rules [8,10,19,20]. Related work in moirélike photonic lattice is arousing more interest due to its unique property.…”
Section: Introductionmentioning
confidence: 99%